A review of EVs charging: From the perspective of energy optimization, optimization approaches, and charging techniques. (July 2018) - Amjad, Muhammad; Ahmad, Ayaz; Rehmani, Mubashir Husain; Umer, Tariq
Highlights: Different energy optimization approaches for EVs charging has been discussed in detail. EVs charging approaches (centralized, distributed, and hybrid) have been explored in detail. Optimization approaches for EVs charging to support the different objective functions have been surveyed. Comparative view of optimized and un-optimized EVs charging has also been provided. Abstract: Introduction of electric vehicles (EVs) or plug-in electric vehicles (PEVs) in the road transportation can significantly reduce the carbon emission. Hence, the demand of EVs is likely to increase in the near future. Large penetration of EVs will also ultimately result into high loads on the existing power grids. The controlled charging of EVs can have a significant impact on the power grid load, voltage, frequency, and power losses. In this paper, we have provided a comprehensive review of various energy optimization approaches used for EVs charging. Energy optimization approaches used for EVs not only enhance the battery life but also contribute in regulating the voltage and frequency. During EVs charging, various objective functions such as supporting the renewable energy sources, minimization of the peak load, energy cost, and maximization of the aggregator profit have also been studied from optimization perspectives. The controlled and an optimized EVs charging enhances the performance of EVs batteries and conserves the energy in the system by minimizing the load and power losses. The different EVs charging approaches such as centralized and distributed suited for different objective functions have also been studied and compared with respect to various optimization approaches.